American Marxism [compact disc, unabridged] - Levin, Mark R. (Mark Reed), 1957- (Simon & Schuster, 2021)
Fox News and radio host Mark R. Levin explains how the core elements of Marxist ideology are now pervasive in American society and culture, from our schools, the press, and corporations, to Hollywood, the Democratic Party, and the Biden presidency, and how it is often cloaked in deceptive labels like "progressivism," "democratic socialism," "social activism," and more. Levin digs into the psychology and tactics of these movements, the widespread brainwashing of students, the anti-American purposes of Critical Race Theory and the Green New Deal, and the escalation of repression and censorship to silence opposing voices and enforce conformity. Levin exposes many of the institutions, intellectuals, scholars, and activists who are leading this revolution, and provides us with some answers and ideas on how to confront them.